2023
DOI: 10.1029/2023je008019
|View full text |Cite
|
Sign up to set email alerts
|

Boulder Diversity in the Nightingale Region of Asteroid (101955) Bennu and Predictions for Physical Properties of the OSIRIS‐REx Sample

Erica R. Jawin,
Ronald‐L. Ballouz,
Andrew J. Ryan
et al.

Abstract: The sample of asteroid (101955) Bennu was collected from the Nightingale sample site by the Origins, Spectral Interpretation, Resource Identification, and Security–Regolith Explorer spacecraft and arrived on Earth on 24 September 2023. To better understand Bennu's parent body, we identified boulders over 2 m in diameter around the Nightingale region and analyzed normal albedo, morphology, and surface roughness. We found that boulders can be separated into two groups based on albedo, and four groups using morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(117 reference statements)
0
3
0
Order By: Relevance
“…This value is consistent with a median regolith particle size of ∼0.5-2.0 cm, which is within the range of particle sizes observed in high-resolution images of Nightingale (Burke et al 2021) and in photos of particles drifting out of the TAGSAM following sample collection (Lauretta et al 2022). The rocks and fine particles in Hokioi Crater and at the TAG contact location are predominantly of the darker lithology, excavated from <1.5 m depth during the formation of the crater, and secondarily of the brighter lithology, likely derived from regolith surrounding the crater (Barnouin et al 2022;Lauretta et al 2022;Jawin et al 2023). Further interpretation of the physical properties of individual boulders and fine regolith has been somewhat limited by the spot size of observations obtained by the OSIRIS-REx Thermal Emission Spectrometer (OTES; Christensen et al 2018).…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…This value is consistent with a median regolith particle size of ∼0.5-2.0 cm, which is within the range of particle sizes observed in high-resolution images of Nightingale (Burke et al 2021) and in photos of particles drifting out of the TAGSAM following sample collection (Lauretta et al 2022). The rocks and fine particles in Hokioi Crater and at the TAG contact location are predominantly of the darker lithology, excavated from <1.5 m depth during the formation of the crater, and secondarily of the brighter lithology, likely derived from regolith surrounding the crater (Barnouin et al 2022;Lauretta et al 2022;Jawin et al 2023). Further interpretation of the physical properties of individual boulders and fine regolith has been somewhat limited by the spot size of observations obtained by the OSIRIS-REx Thermal Emission Spectrometer (OTES; Christensen et al 2018).…”
Section: Introductionmentioning
confidence: 54%
“…similar to those of Bennu (Hamilton et al 2019). A more recent study of Bennu's boulders indicated that the two dominant types may consist of multiple distinct subtypes on the basis of morphology and roughness (Jawin et al 2023); the dark boulders are subdivided into boulder Types A and B, while the bright boulders are subdivided into Types C and D, largely on the basis of morphology. It is not yet known if these subtypes are also distinct in thermal and physical properties.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation